PENGARUH CITRA MEREK, PROMOSI, KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA OJEK ONLINE (Studi pada Pengguna Gojek Mahasiswa Unisbank Semarang) - Sumiarsih, 15.05.51.0224; Maskur, Ali (Students' Journal of Economic and Management, 2019)
The purpose of this study is to test and analyze the influence of brand image, promotion, service quality and price perception on purchasing decisions. This research was conducted at Stikubank University, UNISBANK, Semarang.The population in this study was the Gojek Online motorcycle taxi service user at Stikubank University in UNISBANK Semarang with a population of 100 people. The sampling technique used in this study was purposive sampling method with a total sample of 96 people. This study uses primary data with data collection techniques using a questionnaire. Data were analyzed using validity test, reliability test, multiple regression analysis, F test, determination coefficient test (R2), t test, which was then processed using the SPSS 16 computer program.The results showed that brand image has a positive and significant effect on purchasing decisions, promotion has a positive and significant effect on purchasing decisions. Service quality has a positive and significant effect on purchasing decisions, price perception has a positive and significant effect on purchasing decision.